Back to the classics: R-evolution towards statistical equilibria - Bruno Miller Theodosio; Jan Weber (University of Duisburg-Essen, Institute for Socio-Economics (ifso), 2023)
Economic modeling struggles often with a lack of realism. The reason for that is that economic theory for the last 100 years has focused on simplifying assumptions which reduced important aspects of the economic reality. Concentrating on fix-point solutions and external statistical shocks prevented the profession from accurately describing the economy as a complex system with characteristics like feedback mechanism, evolution, and emergence. We propose a re-evaluation of major findings in the Classical economic literature. The classical literature described the economic system as inherently probabilistic. In this spirit, we discuss the importance of statistical equilibrium models as one way to model complex economic systems in a probabilistic way.
Keywords: B12; B41; C18; D59; 330